Canadian Author Study: Pre-service Teachers Engage in Assignments to Promote Awareness of Canadian Young Adult Literature - McQuirter Scott, Ruth (Brock education, 2004)
This article describes an initiative designed to familiarize pre-service teachers with a wide range of Canadian authors of young adult literature. Teacher candidates work in small groups to study at least three novels by the same author. Each group presents its findings in a creative manner to the class. This background material is then used to prepare a language unit that focuses on one of the following: the author, common themes, or interdisciplinary connections.